COMMUNITY, ADAT, AND ISLAMIC LAW: - Dedisyah Putra; Asrul Hamid (State of Islamic Institute Langsa, 2021)
This article examines the practices of waqf that manage by the mosque in Siantar by comparing the adat law and Islamic law. This study used a qualitative descriptive method in the form of field research which aimed to find out the management of waqf funds carried out by Nazir of Mosque Jami' Darussalam Siantar city and a review of customary law and Islamic law on these activities. The results of the management of waqf land are intended for renovation and maintenance of mosque facilities and infrastructure while cooperation conducted in form of muzara’ah muthlaqah according to most Islamic jurisprudence scholars is mubah (may) caused by a contract of muzara’ah based on and aimed to help and prosper each other between both parties. In customary review, it showed that this management of rice fields has been for a long time with a system that has not changed even though the management of the mosque has changed. Controlling social that comes from the community makes the mosque function as it should to always be maintained, cared for, and prospered.